Review of Safety Equipment in Shipping (Float Tools) in The KMP. Tanjung Burang, on Ulee Lheue – Balohan Tracking - Chairul Insani Ilham; Broto Priyono; Ryan Havis (Politeknik Transportasi Sungai, Danau dan Penyeberangan Palembang, 2019)
The Ulee Lheue Ferry Port is managed by the Department of Transportation port city of Banda Aceh. The crossing port serves two tracks with 3 Ro-Ro ship operating and ship jetfoil 2. One important component in ferry transport is safety. Safety is not only to the service user but also to the crew. On ships operating in the Ulee Lheue Ferry Port there are many safety devices such damaged lifejacket, lifebuoy, lifeboat and the number of safety devices that do not fit the needs of the vessel based on the Safety Of Life At Sea (SOLAS).The conditions and the amount of safety equipment must be considered in terms of both the feasibility of tools and appropriate equipment so that in the event of emergency safety tools that exist can be used with either as a form of implementation of aspects of the safety of passengers on board. The number and condition of safety equipment that does not comply with the requirements could endanger the safety of lives of the passengers in case of accident. The number of safety devices must be able to accommodate the number of passengers and crew on board.